The influence of inter-granular coupling on the magnetic susceptibility and critical current density of YBa2(Cu1−xAgx)3O7−δ superconductors prepared by ethylene glycol assisted solvothermal approach. Issue 11 (15th August 2016) - Al-Refaei, Nora S.; Saddiq, Amna A.; Hafez, M.
Abstract: Series of YBa2 (Cu1−x Agx )3 O7−δ (0≤x≤0.09) powders were prepared by ethylene glycol assisted solvothermal approach. X-ray diffraction verified the formation of single phase crystal structure for all the investigated samples, implying the complete solubility of the silver ions into YBa2 Cu3 O7 . The partial substitution of the Ag atoms into the Cu sites caused a decrease of the lattice constant (c) and an increase of the lattice constants, a, and, b, to preserve the orthorhombic crystal structure of YBa2 Cu3 O7 . The scanning electron microscopy depicted that the incorporation of silver ions into copper sites adjusts the random orientations of the YBCO grains and suppresses the formation of grain boundary. The AC magnetic susceptibility measurement revealed that the superconducting performance of the YBa2 Cu3 O7 is preserved at all Ag concentrations. The critical current density, Jc, measurement revealed that the addition of the Ag into the YBCO caused a strong pinning force is established due to the strong coupling among the grains instead of the weak Josephson junctions and in turn a remarkable increase of the zero field Jc from 2.7 MA/cm 2 to 9.1 MA/cm 2 was achieved.